Modeling the Electronic Structure and Composition Tungsten Adsorbed Metal Complexes of on the Electrode Surface under Conditions of High-Temperature Electrochemical Synthesis - Solyanik, Liudmyla; Kuznetsova, Tetiana; Solovyova, Nataliia; Usenko, Dmytro (International Journal of Engineering and Technology, 2018)
The interest to the physics of nano-dimensional structures, the most urgent and most dynamically developing field of modern solid state physics, is connected both with completely new fundamental scientific problems and physical phenomena, and with the prospects of creating entirely new quantum devices and systems with wide functional opportunities for nano-electronics, measuring equipment, new-generation information technologies, communication equipment, etc.Â Â Â